A new rain attenuation conversion technique for tropical regions - Abd Rahman, Tharek (2010)
Rain attenuation is one of the most crucial factors to be considered in the link budget estimation for microwave satellite communication systems, operating at frequencies above 10 GHz. This paper presents a mathematical model for converting terrestrial rain attenuation data to be used for satellite applications at Ku-band. In the proposed technique, the ITU-R P 618-9, together with a combination of ITU-R P 530-12 and the revised Moupfouma model have been adopted for satellite and terrestrial rain attenuation predictions, respectively. The model has been used for transforming the measured rain attenuation data of some DIGI MINI-LINKS operating at 15 GHz in Malaysia, to be used for MEASAT 2 applications. It was found that the model predictions are fairly reasonable when compared with direct beacon measurements in Malaysia and similar tropical locations. The model will provide a relatively accurate method for transforming the measured terrestrial rain attenuation to be used for satellite applications; and therefore substantially reduce the cost of implementing Earth-satellite links in some tropical regions that have suffcient rain attenuation data for the terrestrial links.